Measurement of AC and DC relaxation properties in polyvinyl chloride (PVC) nanocomposites. (March 2019) - Rajesh,; Kaur, Dalveer; Gaur, M.S.; Goyal, Pankaj; Tiwari, R.K.; Rogachev, A.A.; Rogachev, A.V.
Highlights: AFM images illustrate the modification of structural morphology of PVC matrix. Incorporation of SiO2 NPs and MMT in the PVC matrix tunes its electrical properties. FTIR spectra shows that large number of delocalized state. TSDC peaks are originated due to α-relaxation and MWS relaxation process. Abstract: In present investigation, thin film of polyvinylchloride (PVC)/silicon dioxide (SiO2 )/montomorillonite (MMT) nanocomposites were prepared by solution casting method. AFM analyzed the grain size, particle size, roughness and dispersion of nanofillers in PVC nanocomposites. However, FTIR describes the molecular interaction of nanofillers in PVC structure. The AC and DC relaxation properties of these nanocomposites were measured by means of dielectric spectroscopy and thermally stimulated discharge current (TSDC) respectively. The dielectric spectroscopy has been applied to measure dielectric constant and tangential loss at different frequencies and temperatures; then, it has been specified the effectiveness of nanoparticles on dielectric performance as compared with pure PVC. The permittivity of these nanocomposites is enhanced remarkably, which can be understood by the interfacial polarization effect. The high dielectric constant of value 37 is obtained in the nanocomposite with 4 wt.% MMT at 50 Hz. The temperature dependent dielectric constant could be explained on the basis of free volume available for free charge carriers and MWS relaxation process. The dielectric characteristics are highly influenced by nature of fillers and can be understand by the frequency and temperature dependence of the interfacial relaxation. TSDC peaks are originated due to α-relaxation process and MWS relaxation process.